2016
DOI: 10.7717/peerj.2477
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing ofStreptococcus pneumoniae: development, evaluation and verification of targets for serogroup and serotype prediction using an automated pipeline

Abstract: Streptococcus pneumoniae typically express one of 92 serologically distinct capsule polysaccharide (cps) types (serotypes). Some of these serotypes are closely related to each other; using the commercially available typing antisera, these are assigned to common serogroups containing types that show cross-reactivity. In this serotyping scheme, factor antisera are used to allocate serotypes within a serogroup, based on patterns of reactions. This serotyping method is technically demanding, requires considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(187 citation statements)
references
References 55 publications
1
184
1
1
Order By: Relevance
“…To compare the genomic characteristics of serotype 15A-ST63 isolates from Japan with those of isolates from the United Kingdom, the United States, and Canada, we downloaded whole-genome read data from the Sequence Read Archive database (http://www.ncbi.nlm.nih.gov/sra/) (Technical Appendix Table 1) ( 5 , 8 , 24 , 25 ). To confirm that the data were from serotype 15A-ST63 isolates, we conducted a de novo assembly by using SPAdes ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…To compare the genomic characteristics of serotype 15A-ST63 isolates from Japan with those of isolates from the United Kingdom, the United States, and Canada, we downloaded whole-genome read data from the Sequence Read Archive database (http://www.ncbi.nlm.nih.gov/sra/) (Technical Appendix Table 1) ( 5 , 8 , 24 , 25 ). To confirm that the data were from serotype 15A-ST63 isolates, we conducted a de novo assembly by using SPAdes ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…WGS serotype was derived from the data using a version of PneumoCaT (Kapatai et al, 2016; https://github.com/phe-bioinformatics/PneumoCaT) incorporated as the final analytic stage of the in-house S. pneumoniae WGS bioinformatics pipeline. Specific to this study, the PneumoCaT workflow initially mapped reads from the subject to a reference database containing capsular operon sequences for all serotypes, including serogroup 33 capsular operon sequences and the tts sequence.…”
Section: Methodsmentioning
confidence: 99%
“…This is of benefit to the surveillance of circulating pneumococcal serotypes, since recent studies have identified a decrease in the numbers and prevalence of PCV13 serotypes and a gradual increase in the numbers of nonconjugate vaccine types. Indeed, the 2011-2015 UK national surveillance figures for the serotype distribution of pneumococci causing invasive disease show that the 10 most prevalent serotypes isolated and referred to Public Health England (PHE) for serotyping were serotypes 8, 12F, 3, 22F, 19A, 9N, 15A, 7F, 33F, and 10A (44). Of these 10 serotypes, only serotypes 3, 7F, and 19A are covered by PCV13.…”
Section: Discussionmentioning
confidence: 99%